2014
DOI: 10.1116/1.4896759
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of pore stuffing and unstuffing for postporosity plasma protection of low-k materials

Abstract: Residue growth on metallic hard mask after dielectric etching in fluorocarbon based plasmas. II. SolutionsThe problem of k-value degradation (plasma damage) is a key issue for the integration, and it is becoming more challenging as the dielectric constant of low-k materials scales down. One way to circumvent this issue is temporarily conversion of low-k material from a porous to a dense state by filling the pores with a sacrificial polymer after the deposition and curing of the low-k material. A detailed proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…5, confirming our previous conclusion based on FTIR characterization. For non-protected samples, the κ-value degrades faster with C-free plasmas (SF 6 and NF 3 gas discharges). With pore stuffing, the k value degradation is significantly reduced for all the recipes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…5, confirming our previous conclusion based on FTIR characterization. For non-protected samples, the κ-value degrades faster with C-free plasmas (SF 6 and NF 3 gas discharges). With pore stuffing, the k value degradation is significantly reduced for all the recipes.…”
Section: Resultsmentioning
confidence: 97%
“…Evaluation details including spectrum and elemental analysis were discussed in complementary paper (Ref. 6). Table I shows the properties of pristine and PMMA stuffed samples, which will be used for plasma resistance tests.…”
Section: Methodsmentioning
confidence: 99%
“…The pore stuffing process consists of (i) densification of the porous low-k film by wet stuffing with a sacrificial polymer filling agent (PMMA); (ii) CF 4 plasma etch; and (iii) a thermal burnout process at 450°C for 15 min in N 2 ambient to remove the PMMA. It has been observed that the plasma-induced Si-CH 3 depletion is significantly reduced via pore stuffing and that the silanol groups can be confined to the top surface of the porous film [14]. Afterwards, a wet cleaning procedure was applied in order to remove the post-etch polymer residues and to make the surface more hydrophilic.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Low-k etch was then performed using a CF 4 plasma. PMMA was selected as the pore stuffing chemistry because it decomposes thermally without leaving residues behind (no C@C sp2 formation) [14]. The pore stuffing process consists of (i) densification of the porous low-k film by wet stuffing with a sacrificial polymer filling agent (PMMA); (ii) CF 4 plasma etch; and (iii) a thermal burnout process at 450°C for 15 min in N 2 ambient to remove the PMMA.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation